The Representation of Social Actors in EFL Textbooks: Systemic Functional Linguistics Perspective - Stanislaus Guna; Hieronimus Canggung Darong (Indonesian Journal of EFL and Linguistics, 2023)
Systemic Functional Linguistics (SFL) has gained popularity as a linguistic theory, especially in the field of education where it provides a useful method for examining textbooks. The goal of this study is to examine how social actors are portrayed in a particular textbook utilizing SFL framework. Textual data were gathered from a sample of the textbook, and transitivity patterns of process categories and pronoun usage were used to analyze the data. The results revealed that the pronoun "he" was primarily utilized and that the material process, which denotes physical actions, was most commonly used, depicting men as the main actors. These results imply that the texts in the textbook reflect how social actors are portrayed and represented in speech and offer an understanding of their functions, choices, agency, and relations